Referral Patterns and Outcome of Patients With Synchronous Brain Metastases From Non-small Cell Lung Cancer Treated With Gamma Knife Radiosurgery in a Third-Line Treatment Centre in The Netherlands – A Retrospective Analysis. Issue 1 (January 2020) - ten Berge, D.M.H.J.; Aarts, M.J.; Hanssens, P.E.J.; Beute, G.N.; Aerts, J.G.J.V.; Kloover, J.S.
Abstract: Aims: Little understanding exists of referral patterns for patients with brain metastasis from non-small cell lung cancer (NSCLC) towards treatment with Gamma Knife radiosurgery (GKRS). Therefore, we explored current clinical daily practice and prognosis. Material and methods: In total, 1129 patients with synchronously diagnosed brain metastasis from NSCLC diagnosed between 2008 and 2014 were selected from the population-based Netherlands Cancer Registry; 242 patients were treated with GKRS. Results: Patients receiving GKRS were younger (62 years versus 64 years) and had lower tumour burden: the presence of T2 was higher and T4 was lower (43% versus 33%; P = 0.0158, 19% versus 28%; P = 0.0044, respectively). They more frequently had cN0 (32% versus 19%; P ≤ 0.0001), less frequently had N3 disease (18% versus 29%; P = 0.0004) and there were fewer metastatic sites. In multivariable logistic regression analysis, only age ≤60 years (odds ratio 1.4; 95% confidence interval 1.0–2.0) and patients with N0 stage, compared with those with N2, N3 and NX (odds ratio 0.6 [0.4–0.9], 0.3 [0.2–0.6], 0.3 [0.1–0.6], respectively), were more likely to receive GKRS. Gender, T-stage, histology, number of comorbidities, country of birth as proxy for ethnicity and socioeconomic status were not associated. The median survival was 9.6 months after GKRS versus 4.0 months in the noGKRS group (Log-rank: P ≤ 0.0001). Multivariably, GKRS, female, lower T-/N-stage, <2 comorbidities, adenocarcinoma and higher socioeconomic status were associated with a significantly reduced hazard of death. For the patients with at least one follow-up magnetic resonance image (80%), local intracranial tumour control was achieved in 93% at the last follow-up. Conclusion: Patients presenting with synchronic brain metastasis from NSCLC who are referred to a third-line treatment centre for GKRS are younger and have a lower tumour load. Due to a high level of local control, GKRS is able to provide a significant window of opportunity for additional treatment of the primary tumour. Highlights: Providing insight into referral patterns for GKRS for brain metastasis from NSCLC. Referred patients are younger and have a lower tumour burden. High intracranial local tumour control is achieved after treatment with GKRS. The current patient flow results in prolonged survival.